Fibromyalgia in the light of different methods of treatment - Szota, Maciej; Modlińska, Aleksandra; Rogacka, Karolina; Kędziora–Kornatowska, Kornelia (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Fibromyalgia is a disease with many symptoms that are difficult to treat. The most troublesome element is muscle, bone or joint pain. Importantly, the diagnosis of this disease is based on the physical examination and the subjective examination, which shows that there are no laboratory tests to confirm its presence. Public awareness of fibromyalgia is negligible, while more research is needed on the treatment of this disease and the possible alternatives associated with it. The aim of this study was to analyze the available literature on the basis of the PubMed scientific database, considering only scientific articles that were published within the last 5 years. The following keywords were used: fibromyalgia and physiotherapy, fibromyalgia and cannabis, fibromyalgia and cytokines. Description of the state of knowledge: Treatments related to cannabinoids and physiotherapy are still developing fields of knowledge. More than 40 papers related to the topic of the study were used for the review. The need for further research is apparent, especially randomized studies in which allocation to an experimental or control group is completely random. The question of investigating the long-term effectiveness of a given treatment is also not negligible, as many studies do not have a so-called follow-up. Conclusion: Cannabinoids are effective in the treatment of complaints associated with fibromyalgia. Exercise, laser therapy and acupuncture reduce pain and improve quality of life in patients with fibromyalgia. More research on this disease is needed, especially with larger patient groups.